Viscous flow and heat transfer through two coaxial porous cylinders - Hona, J; Pemha, E; Nyobe, E (The International Journal of Multiphysics, 2015)
In this paper, a flow of a high viscous fluid with temperature-dependent viscosity through a porous industrial conduct is investigated by means of similarity transformation technique. The problem is modeled using mass, momentum and energy conservations. The variation of viscosity as function of temperature couples the vorticity equation to the energy equation. The numerical procedure for solving the differential equations of the problem is detailed. For low values of the main control parameters, the analytical solution of the problem is yielded. It appears from the numerical results of the problem that the variations of temperature are stopped in a large area around the middle of the flow domain. The maxima of thermal gradients are situated at the walls due to suction. The dominance of flow reversal agrees with the behavior of the normal pressure gradient inside the annular conduct.